Theoretical Insights into the Selective Extraction of Americium(III) over Europium(III) with Dithioamide-Based Ligands - Wang, Cui; Wu, Qun-Yan; Kong, Xiang-He; Wang, Cong-Zhi; Lan, Jian-Hui; Nie, Chang-Ming; Chai, Zhi-Fang; Shi, Wei-Qun (Inorganic chemistry, 2019)
Separation of trivalent actinides An(III) from lanthanides Ln(III) is a worldwide challenge owing to their very similar chemical behaviors. It is highly desirable to understand the nature of selectivity for the An(III)/Ln(III) separation with various ligands through theoretical calculations because of their radiotoxicity and experimental difficulties. In this work, we have investigated three dithioamide-based ligands and their extraction behaviors with Am(III) and Eu(III) ions using the scalar-relativistic density functional theory. The results show that the dithioamide-based ligands have stronger electron donating ability than do the corresponding diamide-based ones. All analyses including geometry, Mulliken population, QTAIM (quantum theory of atoms in molecules), and NBO (natural bond orbital) suggest that the Am–S/N bonds possess more covalency compared to the Eu–S/N bonds, and the M–S bonds have more covalent character than the M–N bonds. Thermodynamic results reveal that N 2,N 9-diethyl-N 2,N 9-di-p-tolyl-1,10-phenanthroline-2,9-bis(carbothioamide) (L 1 ) has a stronger complexing ability with metal ions owing to its rigid structure and that N 6,N 6′-diethyl-N 6,N 6′-di-p-tolyl-[2,2′-bipyridine]-6,6′-bis(carbothioamide) (L 2 ) shows a higher selectivity for the Am(III)/Eu(III) separation. In addition, these dithioamide-based ligands possess Am(III)/Eu(III) selectivity higher than those of the corresponding diamide-based ones, although the former have weaker complexing ability with metal ions, probably due to the greater covalency of the M–S bonds. This theoretical evaluation provides valuable insights into the nature of the selectivity for the Am(III)/Eu(III) separation and information on designing of efficient An(III)/Ln(III) separation with dithioamide-based ligands.